The Effect of the Number of Third-Party Funds and Financing Provided on Bank Liquidity (Case Study of PT Bank Sumut Sub-Branch Office of Medan Katamso) - Ka’u, Novariany; Lathief Ilhamy Nasution, Muhammad (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study aims to determine the relationship and influence of Third-Party Funds (DPK) and financing provided on liquidity in Bank Sumut Sub-Branch Office of Medan Katamso. The type of research used in this research is quantitative research. This research relates to the variable Third-Party Funds (DPK) as the independent variable and Liquidity as the dependent variable. The data used in this research is time series data for the period January 2018-2021. While the data samples taken are data on third-party funds and the financing-to-deposit ratio by recording all the data listed in the reports for quarter I to quarter IV for 2018-2021 at Bank Sumut online at the address https://www.banksumut.co.id. In this study, the independent variable (Free/X) is Third-Party Funds (DPK). While the dependent variable (Bound/Y) in this study is Liquidity (FDR/Financing to Deposit Ratio). The calculation of the variables was carried out using the SPSS version 23.0 program. The results of this study indicate that partially Third-Party Funds have a significant influence on the Liquidity of Bank Sumut Sub-Branch Office of Medan Katamso and Financing Provided has a significant influence on Bank Sumut Sub-Branch Office of Medan Katamso. Whereas, simultaneously Third-Party Funds and Financing Provided jointly have a significant effect on the liquidity of Bank Sumut Sub-Branch Office of Medan Katamso.